2002
DOI: 10.1046/j.1365-2427.2003.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical flow velocities for the growth and dominance of Anabaena circinalis in some turbid freshwater rivers

Abstract: SUMMARY 1. From measurements at several weir pool sites along the turbid and freshwater Barwon‐Darling River, Australia, the development of persistent stratification (for periods of >5 days) was related to river discharge. For the sites examined, the required discharge to allow the development of persistent stratification was between 100 and 450 ML day−1 during the hotter months. High discharge during the hotter months did not allow the formation of persistent stratification, although diel stratification did o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(73 citation statements)
references
References 15 publications
(26 reference statements)
2
68
0
Order By: Relevance
“…Westwood and Ganf (2004) found that Dolichospermum circinale (Anabaena circinalis) populations grew faster when exposed to persistent stratification than under diurnally stratified or mixed conditions in the lower Murray River, Australia. A flow rate of only 0.05 m s À1 was observed to be sufficient to prevent the persistent stratification needed for cyanobacterial growth (Mitrovic et al, 2003). Several enclosure experiments showed that the growth of Dolichospermum populations reduced with artificial mixing under a non-stratified regime (Reynolds et al, 1983;Nakano et al, 2001).…”
Section: Climate Change Associated With Dolichospermum Bloomsmentioning
confidence: 94%
“…Westwood and Ganf (2004) found that Dolichospermum circinale (Anabaena circinalis) populations grew faster when exposed to persistent stratification than under diurnally stratified or mixed conditions in the lower Murray River, Australia. A flow rate of only 0.05 m s À1 was observed to be sufficient to prevent the persistent stratification needed for cyanobacterial growth (Mitrovic et al, 2003). Several enclosure experiments showed that the growth of Dolichospermum populations reduced with artificial mixing under a non-stratified regime (Reynolds et al, 1983;Nakano et al, 2001).…”
Section: Climate Change Associated With Dolichospermum Bloomsmentioning
confidence: 94%
“…High water temperatures have been known to lead to cyanobacterial bloom development in temperate (Robarts andZohary, 1987 Jöhnk et al, 2008;Wu et al, 2014) and semi-arid (Mitrovic et al, 2003) regions. The genus Microcystis is one of the most important cyanobacteria due to its great ecological importance and public health implications (Sanchis et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…They took place during periods of low flow and thermal stratification. In Australia, the blooms of Anabaena occurred in the River Murray-Darling, and Murrumbidgee (Mitrovic et al 2003). Some of the blooms contained saxitoxin produced by Anabaena circinalis.…”
Section: Introductionmentioning
confidence: 99%